Evaluation of anatomical and visual function for early detection of ethambutol toxicity among tuberculosis patients - Tevaraj, Jessica Mani Penny; Tan, Chai Keong; Tai, Evelyn Li Min; Muhammed, Julieana; Mohd Noor, Raja Azmi; Wan Hitam, Wan Hazabbah (Press of International Journal of Ophthalmology (IJO PRESS), 2017)
AIM: To evaluate if early ethambutol toxicity can be detected by comparing pre - and post - treatment anatomical and visual function using retinal nerve fiber thickness, pattern visual evoked potentials and conventional optic nerve function tests. METHODS:This was a prospective study involving 72 eyes of 36 patients treated with ethambutol according to directly observed treatment short-course(DOTS) strategy in Hospital Universiti Sains Malaysia, Kelantan, Malaysia. The visual acuity and optic nerve function tests were performed by a single investigator. Likewise, Humphrey automated perimetry, optical coherence tomography ( OCT ) measurement of the retinal nerve fibre layer (RNFL) and pattern visual evoked potential (PVEP) were performed by a single technician. The examinations were performed before initiating ethambutol treatment and 3mo after that. RESULTS: There was no change in visual acuity, colour vision, light brightness, red saturation and fundus findings pre and post ethambutol. However, there was a statistically significant deterioration in the mean deviation of the visual field post treatment (P = 0. 010). There were also significant changes on OCT and PVEP, with increased RNFL thickness in all quadrants ( P < 0. 05 ) and PVEP delayed P100 peak latency and amplitude (P<0. 001). CONCLUSION: Ethambutol toxicity is a known complication of tuberculosis treatment. Early detection of this toxicity may prevent severe irreversible visual loss. The use of OCT to detect RNFL thickness and PVEP to assess P100 latency and amplitude can assist in the detection of subclinical anatomical and visual function changes prior to development of abnormalities on conventional optic nerve function tests.